STRENGTHENING THE ROLE OF ELEMENTS OF FINANCIAL CONTROL OF ENTERPRISES WHILE IMPROVING TAX COLLECTION - Nuriddin, Ernazarov; Bahriddinxon, Yahyoyev (Antis Publisher, 2024)
The article outlines the difficulties of ensuring stability, the unpredictability of a cyclical downturn in the economy, methods of monetary control in conditions of both budget deficits and surpluses in conditions of manipulation of securities through the use of a reserve requirement for bank deposits. It is noted that mandatory reserve requirements should not be a permanent element of the state financial system. The proposal is made that reserve requirements in the order of 5% of credit accumulated in current accounts or savings deposits should be subject to monetary control rather than budgetary control